The Advancing Assessment of Power System Stability Using Smart Grid Technology - Murat Merekenov,Karmel TokhtibakiyevmAnur Bektimirov (International Journal of Advanced Science and Technology, 2020)
The paper proposes new method for assessment of power system stability. New method based on advancing approach to determination of stability limits. The paper represents more accurate and reliable ways to determine limits for power transmission through the grid. Nowadays, the static stability limits formed by using special software which solves nonlinear equations of the electrical system. Power systems control power flows through the power lines for avoiding black outs by using automated control systems. Automation thresholds depend on the maximum power transmitted through the line or section, and the maximum transmitted power is calculated using the iterative methods. But the calculations in this way are not sufficiently accurate and flexible, since the calculations are done for the entire system, and not for each section individually. And it means the limits on certain sections and lines can vary. The proposed method differs from the existing one in a way it determines the limits using the angle shift between the voltage phasors in the nodes in real time. It makes possible to more deeply and adaptively manage. Also proposed new control algorithms which determines stability boundaries in advance. Algorithm was verified through experimental studies on physical model of the power system.